IDENTIFICATION OF ODOR COMPONENTS OF AGARWOOD (Jurnal Teknologi (Sciences & Engineering), 2015)
This article presents the use of Z-score in assessing the significant chemical compounds extracted by head space solid phase microextraction (HS-SPME) and gas chromatography – mass spectrometry (GC-MS) analysis of an agarwood oil obtained from Melaka, Malaysia. Two types of SPME fiber; polydimethylsiloxane (PDMS) and divinylbenzene-carboxen-polydimethylsiloxane (DVB-CAR-PDMS) were used. During the extraction analysis, the results showed that at least 27 and 29 compounds were identified using PDMS and DVB-CAR-PDMS fiber, respectively. DVB-CAR-PDMS fiber was found to be more efficient in terms of selectivity of compounds extraction. The application of Z-score showed that eight and eleven marker compounds were determined in PDMS and DVB-CAR-PDMS fibers, respectively. 4-Phenyl-2-butanone, a-guaiene, β-agarofuran, a-bulnesene, a-agarofuran and 10-epi-g-eudesmol were some of the compounds selected and were often reported significantly in agarwood oils as key odor compounds. The information gathered will be used for compound selection towards grading of agarwood oils by sensor technology.
Keywords: Agarwood; chemical constituents; HS-SPME-GCMS; Z-score